Dr. Renu Modi and Prof. Dr. Clarissa Vierke about India-Africa relations - Modi, Renu; Vierke, Clarissa (Cluster Conversations, 2025)
In this latest episode of the Cluster Conversations, fellow Dr. Renu Modi talks with her host Prof. Dr. Clarissa Vierke about her recent fellowship with the Cluster of Excellence in Bayreuth. Modi also reflects on three decades of India-Africa relations, highlighting how economic cooperation and cultural exchange have reshaped the landscape of South-South collaboration. From her stay in Bayreuth, she contrasts African Studies in India and Germany, uncovering unique differences in focus – from pragmatic development to rich cultural and religious studies. The fellow-host-duo also talk about textile trade and "counter-archives," where oral histories, attic finds, and Indian Ocean connections reveal untold stories between the continents. A must-listen for anyone curious about global interconnections, hidden histories, and the evolving meaning of solidarity.